Determinants of Bottle-Feeding: Experience in a Tertiary Care Hospital - Hasan, Md Rabiul; Azad, Md Tarek; Dev, Archana; Hussain, Md Muazzem; Das, Ashith Chandra; Rahman, Zainab (Jalalabad Medical Journal, 2025)
Feeding practice is crucial in a child's life. Many women don't know that giving infants bottle-feeding has consequences. Though bottle-feeding practice is discouraged among mothers, the use of bottles in infant feeding practice is still high. The objective of this study was to assess the determining factors for bottle-feeding in one- to twelve-month-old infants admitted to the paediatric ward at Jalalabad Ragib-Rabeya Medical College Hospital between the periods of January 2018 to June 2018. For this purpose, 128 mothers were purposively interviewed. A pre-formed questionnaire was used for data collection. Infants' and mothers' demographic variables and feeding practices were documented and analysed. Bottle-feeding is more com mon in older infants (10-12 months). Infants born in private clinics and with caesarean sections were more likely to feed bottles (p<0.05). Older, educated, and working mothers had more tendencies to use the bottle with their infants. Birth order and family income had an influence on feeding practices. We also found the influence of dwelling place and maternal BMI on infant feeding. Mothers mentioned that the main reason for giving the bottle to their infants was insufficient breast milk and being influenced by other people. This study reveals bottle-feeding user profiles. The study can be used to plan strategies for child health promotion and prevention of the use of breast milk substitutes. Jalalabad Med J 2024; 21 (1): 11-16